Screening spreading depolarizations during epilepsy surgery - Santos, Edgar; Dávila-Rodríguez, Daniel Oswaldo; Márquez-Gonzalez, Katia; Díaz-Peregrino, Roberto; Alonso-Vanegas, Mario; Olivares-Rivera, Arturo; Anschel, David; San-Juan, Daniel (Acta neurochirurgica, 2019)
BackgroundSpreading depolarization (SD) is a fundamental pathophysiological mechanism of both pannecrotic and selective neuronal lesions following deprivation of energy. SD with brain injury has been reported including in one patient during an intracranial operation. However, the incidence of SDs in operative resections is unknown.MethodsWe performed (a) retrospective analysis of intraoperative AC-recordings of 69 patients and (b) a prospective study using intraoperative near-DC recording. All patients had the diagnosis of pharmaco-resistant epilepsy. Both studies were designed to determine the incidence and characteristics of SDs intraoperatively. In the retrospective analysis, we used intraoperative electrocorticography (iECoG) recordings obtained from AC-recording of 69 patients. In the prospective analysis, we used an Octal Bio Amp and Power Lab ECoG recorder with near-DC range.ResultsIn the retrospective study, we included 69 patients with a mean of 1 h 3 min of iECoG recordings. In the prospective study, we recruited 20 patients with near DC recordings. A total of 35 h 41 min of iECoG recordings with mean of 2 h 32 min/patient were analyzed. We did not find SD in either study.ConclusionsSDs were not detected during intraoperative recordings of epilepsy surgery using AC- or DC-amplifiers.
Gesehen am 04.07.2019